2020
DOI: 10.1016/j.psj.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinoacetic acid supplementation improves feed conversion in broilers subjected to heat stress associated with muscle creatine loading and arginine sparing

Abstract: It was hypothesized that dietary guanidinoacetic acid ( GAA ), the precursor of creatine ( Cr ), would be beneficial to heat-stressed finisher broilers owing to improved cellular energy status and arginine sparing effects. A total of 720 one-day-old male Ross 308 broilers were allocated to 3 treatments, 0 (control), 0.6, or 1.2 g/kg of GAA added to complete corn–soybean meal diets, and were fed for 39 D, with 12 replicates (20 birds each) per treatment. A chronic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…However, only limited information exists regarding the dose-dependent ability for GAA to spare Arg in practical broiler diets, as well as effects on Cr-related metabolites in muscle (i.e., phosphagen concentrations) or glycogen. In terms of Arg-adequate diets, current research indicates that GAA improves growth performance (Michiels et al, 2012; Mousavi et al., 2013; Majdeddin et al, 2017; Cordova-Noboa et al., 2018a,b), but outcomes related to muscle energy reserves like phosphagens or glycogen, or in comparison to animal protein-containing control diets with known Cr content, are scarce (Michiels et al, 2012). Thus, we hypothesized that GAA supplementation would elicit positive effects on growth performance specifically when included in Arg-deficient, practical broiler diets, with additional benefits involving muscle phosphagen concentrations in birds receiving both Arg-deficient and Arg-adequate diets.…”
Section: Introductionmentioning
confidence: 99%
“…However, only limited information exists regarding the dose-dependent ability for GAA to spare Arg in practical broiler diets, as well as effects on Cr-related metabolites in muscle (i.e., phosphagen concentrations) or glycogen. In terms of Arg-adequate diets, current research indicates that GAA improves growth performance (Michiels et al, 2012; Mousavi et al., 2013; Majdeddin et al, 2017; Cordova-Noboa et al., 2018a,b), but outcomes related to muscle energy reserves like phosphagens or glycogen, or in comparison to animal protein-containing control diets with known Cr content, are scarce (Michiels et al, 2012). Thus, we hypothesized that GAA supplementation would elicit positive effects on growth performance specifically when included in Arg-deficient, practical broiler diets, with additional benefits involving muscle phosphagen concentrations in birds receiving both Arg-deficient and Arg-adequate diets.…”
Section: Introductionmentioning
confidence: 99%
“…It may partially compensate for the low ATP as a result of T 3hormone supplementation that might be dissipated in the form of heat loss or as a result of low feed intake. Although muscle Cre concentration was not measured under current study, previous studies showed an increase in muscle Cre level when supplemented with GAA either with or without fish meal supplementation (Lemme et al 2011) or under the stressful condition of cyclic heat stress (Majdeddin et al 2020).…”
Section: Discussionmentioning
confidence: 61%
“…Some previous studies showed that dietary long-term (>35 d) supplementation with GAA at dose rate of 600 to 1,200 mg/kg can improve the feed conversion efficiency and increase body weight gain of broilers ( Michiels et al, 2012 ; Córdova-Noboa et al, 2018 ; He et al, 2019 ), and even under stress condition ( Majdeddin et al, 2020 ). Faraj et al (2014) reported that dietary addition of 4 to 12 g/kg CMH for a trial period of 42 d can improve birds’ growth performance.…”
Section: Discussionmentioning
confidence: 99%